Fungal Diversity in the Soil of the Oxytropis glacialis Root System on the Qinghai-Tibet Plateau - Cao, Peng-xi; Liu, Yixuan; Ma, Hong-mei; Zhao, Ning; Chen, Shu-ting; Xu, Guo-qi; Liu, Xing (Frontiers in Microbiology, 2022)
Because of swainonine-producing endophytic fungal, Oxytropis glacialis is one of the main poisonous weeds in the alpine grassland and desert grassland of the Qinghai-Tibet Plateau (QTP). It has a severe impact on grassland degradation on the QTP. In this paper, the ITS region of fungal communities in the soil of the O. glacialis root system was sequenced by high-throughput sequencing and analyzed by bioinformatics methods. The physical and chemical properties of the soil samples were analyzed in combination with the fungal diversity and its relationship with the soil physical and chemical factors. The results showed that the soil fungal community in the O. glacialis root system are rich in diversity in different ecological environments and are most affected by the soil pH value and organic matter. The swainonine-producing fungal Embellisia oxytropis was first detected in the soil of the O. glacialis root system. This finding provides data to support the next step in demonstrating the horizontal spread of swainone-producing fungal from O. glacialis to soil. In addition, a stable network of core flora has a facilitating effect on the formation of O. glacialis as a dominant species in alpine ecosystems.